Artificial Intelligence for Data Science in Theory and Practice - Alloghani, Mohamed; Thron, Christopher; Subair, Saad.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides valuable information on effective, state-of-the-art techniques and approaches for governments, students, researchers, practitioners, entrepreneurs and teachers in the field of artificial intelligence (AI). The book explains the data and AI, types and properties of data, the relation between AI algorithms and data, what makes data AI ready, steps of data pre-processing, data quality, data storage and data platforms. Therefore, this book will be interested by AI practitioners, academics, researchers, and lecturers in computer science, artificial intelligence, machine learning and data sciences. Presents approaches to artificial intelligence taken by various sectors; Includes development-related applications in AI from around the world; Discusses AI in government, healthcare, education, tourism in addition to AI ethics. .
Introduction -- Part I: Government services -- Intelligent chat bots for online customer service -- Improved services delivery using AI -- Intelligent policing: physical crime and cybercrime prevention and detection -- Part II: Healthcare Services -- Breast cancer diagnosis -- IoT Pharmaceutical management -- Biomedical Text conversion algorithms -- Part III: Education -- Machine learning in teaching and assessment of students -- Prediction of student performance -- Training the next generation of AI students -- Part IV: Tourism and hospitality -- Landmark recognition -- Recommender system for tourists -- Part V: AI Ethics -- Ethics of facial recognition -- Ethics of robotic services -- Bias issues and misapplication of machine learning -- Conclusion.
Keywords: Telecommunication; Machine learning; Computational intelligence; Artificial intelligence; Quantitative research; Communications Engineering, Networks; Machine Learning; Computational Intelligence; Artificial Intelligence; Data Analysis and Big Data; Artificial intelligence -- Data processing